2004
DOI: 10.1021/ic049377m
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclic and Acyclic Diamides:  Comparison of Their Aqueous Phase Binding Constants with Nd(III), Am(III), Pu(IV), Np(V), Pu(VI), and U(VI)

Abstract: This report describes affinity measurements for two, water-soluble, methyl-alkylated diamides incorporating the malonamide functionality, N,N,N',N' tetramethylmalonamide (TMMA) and a bicyclic diamide (1a), toward actinide metal cations (An) in acidic nitrate solutions. Ligand complexation to actinides possessing oxidation states ranging from +3 to +6 was monitored through optical absorbance spectroscopy, and formation constants were obtained from the refinement of the spectrophotometric titration data sets. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 17 publications
4
30
0
Order By: Relevance
“…Studies have shown malonamides to display different binding affinities for different lanthanide ions. 64 Introducing a lower malonamide density on the nanoparticles through incorporation of a mixed ligand shell on the particle surface may facilitate lanthanide selectivity and result in a distinct plasmon signature for each individual ion, as has been shown in the literature for several toxic heavy metal ions. 24 The temporal response of the sensor was measured by monitoring a region of the absorbance spectra corresponding to bicyclic malonamide.…”
Section: Resultsmentioning
confidence: 97%
“…Studies have shown malonamides to display different binding affinities for different lanthanide ions. 64 Introducing a lower malonamide density on the nanoparticles through incorporation of a mixed ligand shell on the particle surface may facilitate lanthanide selectivity and result in a distinct plasmon signature for each individual ion, as has been shown in the literature for several toxic heavy metal ions. 24 The temporal response of the sensor was measured by monitoring a region of the absorbance spectra corresponding to bicyclic malonamide.…”
Section: Resultsmentioning
confidence: 97%
“…This order was the same as that of the stability constants for these metal-ion TMMA complexes in HNO 3 solution. [11] In NaNO 3 media, the K d values of all of the metal ions increased with increasing [NaNO 3 ], except for the K d of Th(IV) in 7 M NaNO 3 . Because TMMA is a neutral ligand, the metal ions must be neutralized by counter-anions that are extracted onto the resin.…”
Section: Uptake Kinetics Of Eu(iii) Th(iv) and U(vi)mentioning
confidence: 95%
“…[2][3][4][5][6][7][8][9][10][11][12][13] Although the chemical components and radioactivity of LLW differ from those of HLW, the selectivity and extraction ability of malonamide derivatives suggested their applicability in the analysis of An in solutions of digested LLWs. Recently, malonamide derivatives have been covalently bonded to a polymer to produce a solid extraction resin for column chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…Chelating diamides have been recognized for a number of years as being affective ligands for solvent extraction of lanthanides and actinides [41][42][43][44][45][46][47][48][49]. Tetraalkyl malonamides and succinamides have been studied in [42,43,[45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…This work was subsequently followed up by work aimed at synthesizing chelating diamide ligands specifically designed for rare earth chelation by controlling the dihedral angle between the two carbonyl groups through the use of a rigid backbone [44]. Ultimately, this led to the development of rigid bicyclic diamides, tailored for the solvent extraction of rare earth cations [41,48,49]. This precedent demonstrates that an aprotic chelating diamide ligand should have good affinity for lanthanide cations.…”
Section: Introductionmentioning
confidence: 99%